Value co-creation intention among consumers at the bottom of the pyramid: A study of rural and community banks in Ghana. Issue 2 (30th April 2021) - Nusenu, Angela Abena; Xiao, Wen; Say, Joy; Opata, Christian Narh
Abstract : We investigated the relationship between consumer satisfaction, trust in firm, interaction, and perceived service quality on value co-creation intention among rural and community bank consumers in Ghana. Participants were a purposive sample of 315 (female = 49. 52%; mean age = 42. 94 years, SD = 14. 47 years). They completed consumer satisfaction, trust in firm, consumer-firm interaction, perceived service quality, and value co-creation intention measures. Structural equation modelling analysis of the data showed that consumer satisfaction strengthens trust in firm, interactions, and value co-creation intention. Further, perceived service quality moderated the relationship between interaction and value co-creation intention. Consumer satisfaction and trust in firm appear to be a resource for consumer-firm interaction and value co-creation intentions with perceived service quality.